Use of high order precursors for manufacturing gate all around devices. (1st November 2017) - Hikavyy, A.; Zyulkov, I.; Mertens, H.; Witters, L.; Loo, R.; Horiguchi, N.
Abstract: Epitaxial growth of strained and defect free SiGe layers grown with disilane and digermane was investigated. This precursors set allows to cover a broad range of Ge concentration (15–65%) at low temperatures (400–550 °C). It was shown that change of carrier gas (from H2 to N2 ) does not increase SiGe growth rate but significantly reduces Ge concentration. Increase of total process pressure considerably reduces SiGe growth rate which is attributed to peculiarities of digermane decomposition and influence of hydrogen surface passivation on disilane decomposition. It was shown that both disilane and digermane can be successfully combined with conventional precursors like silane and germane. These experiments suggested that digermane decomposition is the main driver of the growth rate increase during SiGe growth. Based on the presented data we demonstrated growth of different SiGe/Si and SiGe/Ge stacks with high quality necessary for production of gate all around field effect transistors.